Potential Fraud Detection Analysis of Finansial Statements: Diamond Fraud Approach - Nodeski Yogi Fadli; Junaidi Junaidi (Telaah Bisnis, 2022)
The motivation of this research is the existence of fraud that occurs in the financial reporting of entities both abroad and in Indonesia. This investigation aims to explain the detection of financial statements that have the potential to contain fraud using the Fraud Diamond approach. The sampling method in this research is purposive sampling for companies listed on the Indonesia Stock Exchange. The sample consists of 93 companies during the 2017-2019 financial statement period from the manufacturing industry. The analysis of research is a multiple linear regression model with a quantitative approach. Based on statistical studies, the financial target variable significantly positively affects the potential for fraud. External pressure has a significant negative effect on the potential for financial fraud. In contrast, financial stability, the nature of the industry, effective monitoring, rationalization, and capability have no effect on the potential for financial fraud.